Síndrome Respiratória Aguda Grave: comparação entre a mortalidade por SARS-CoV-2 e agente etiológico não identificado, uma interação com a Teoria do Caos - Queiroz, Flávia (2024)
Objective: To compare mortality between cases of Severe Acute Respiratory Syndrome (SARS) with laboratory identification of SARS-CoV-2 and cases without a defined etiological agent, applying the concepts of Chaos Theory and interaction with the SHELL model. Methods: Descriptive retrospective cohort study carried out with secondary data from SARS notifications by the Hospital Epidemiology Nucleus of the Fundação Faculdade Regional de Medicina de São José do Rio Preto, and obtained from SIVEP-Gripe, with the final outcome being death and classification of SARS due to COVID-19 and unspecified. From the data, a descriptive analysis of the variables was carried out, as well as bivariate statistical analysis using the Chi-square test, a measure of association represented by the Odds Ratio (OR) and the determination of the level of significance (p<0.05) through of the StatsDirect program version 3.3.6 (2023). The SHELL model was adapted in the context of the COVID-19 pandemic to understand the interactions of its components with the health service. Results: A total of 2174 (65%) deaths from SARS due to COVID-19 and 1.196 (35%) deaths from unspecified SARS were reported from March 2020 to December 2022. The comparative analysis of mortality revealed relevant nuances over the years. While 2021 was marked by the highest number of SARS notifications due to COVID-19, only in 2022 was there a statistically significant disparity between deaths from SARS due to COVID-19 (32.81%) and unspecified SARS (13.16%). Regarding sex, the chance of death from SARS due to COVID-19 was 36% higher among men than the chance of death from unspecified SARS. In relation to the age group, a statistically significant difference was observed in the years 2021 and 2022. In 2021, the chance of death from SARS due to COVID-19 in individuals aged ≥ 60 years was 56% lower than the chance of death by unspecified SARS. In 2022, the chance of death from SARS due to COVID-19 in individuals aged ≥ 60 years was 171% greater than the chance of death from unspecified SARS in the same age group. Regarding the presence of risk factors and comorbidities, it was observed in 90.71% of deaths from SARS due to COVID-19 and in 85.70% of deaths due to unspecified SARS, however, no statistical significance was found. Conclusion: The study made it possible to compare mortality from SARS due to COVID-19 and unspecified SARS by identifying annual variations and associated factors such as sex, age group, clinical signs and comorbidities, contributing to a better understanding of mortality related to SARS, especially in the context of COVID-19. Furthermore, the adaptation of the SHELL model to the health service showed that this model can be used to improve health systems, especially in facing challenges such as pandemics, highlighting the importance of epidemiological surveillance and the organization of health services.